2011
DOI: 10.1089/vim.2011.0004
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Requirement for IFN-γ for Respiratory Control and Immunotherapy in Murine Gammaherpesvirus Infection

Abstract: Interferon-g (IFN-g) and perforin (pfp) are important effector mechanisms used by CD8 T cells to clear virusinfected cells. In this study, we used IFN-g/pfp double knockout mice to address if these two effector molecules play redundant roles in the control of acute infection with murine gammaherpesvirus-68 (MHV-68) in BALB/C mice. Perforin knockout (KO) mice and wild-type mice cleared infectious virus from the lungs, even following high-dose infection. However, the IFN-g KO and IFN-g/pfp double knockout (DKO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Our previous work showed that CD4, but not CD8, T cells were critical for the regression of S11 B lymphoma cells latently infected with MHV-68 in BALB/c mice (15). The present study was performed with the C57BL/6 mouse strain, which may partly explain the different findings, given the demonstrated strain dependence of MHV-68-specific T cell responses (5,8). The two cell lines were also generated in different ways, SL1 cell through direct infection of fetal liver-derived B cells, whereas the S11 cell line was cultured from a lymphoma that developed in a long-term-infected mouse.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Our previous work showed that CD4, but not CD8, T cells were critical for the regression of S11 B lymphoma cells latently infected with MHV-68 in BALB/c mice (15). The present study was performed with the C57BL/6 mouse strain, which may partly explain the different findings, given the demonstrated strain dependence of MHV-68-specific T cell responses (5,8). The two cell lines were also generated in different ways, SL1 cell through direct infection of fetal liver-derived B cells, whereas the S11 cell line was cultured from a lymphoma that developed in a long-term-infected mouse.…”
mentioning
confidence: 67%
“…Using the murine gammaherpesvirus 68 (MHV-68, ␥HV-68) mouse model of gamma-2 herpesvirus infection, we now have a good understanding of the immunological factors necessary to control virus replication (1)(2)(3)(4)(5)(6)(7)(8)(9). However, we have a much poorer understanding of T cell recognition of latently infected B cells.…”
mentioning
confidence: 99%
“…CD4 T cells in IRF-1 Ϫ/Ϫ mice are thought to be skewed toward a Th2 phenotype, with decreased expression of IFN-␥ due to attenuated interleukin-12 (IL-12) expression (27). IFN-␥ is induced during the late stages of acute MHV68 infection (28) and facilitates clearance of lytically replicating MHV68 in the lungs (29). Given the importance of IFN-␥ in MHV68 clearance, serum IFN-␥ levels were measured at 9 days postinfection.…”
Section: Resultsmentioning
confidence: 99%
“…1B). Interestingly, IFNγ does protect against lethal infection with murine cytomegalovirus (Pomeroy et al , 1998), dengue virus (Fagundes et al , 2011; Costa et al , 2012) and murine gamma-herpesvirus (Lee et al , 2009; Tsai et al , 2011). In contrast, IFNγ signaling has no discernible impact on survival in response to vesicular stomatitis virus, Semliki forest virus, or influenza virus [Huang et al , 1993; Muller et al , 1994; van den Broek et al , 1995].…”
Section: Resultsmentioning
confidence: 99%